Do depressed and anxious men do groups? What works and what are the barriers to help seeking?. Issue 3 (26th June 2013) - Cramer, Helen; Horwood, Jeremy; Payne, Sarah; Araya, Ricardo; Lester, Helen; Salisbury, Chris
Abstract : Aim: To map the availability and types of depression and anxiety groups, to examine men's experiences and perception of this support as well as the role of health professionals in accessing support. Background: The best ways to support men with depression and anxiety in primary care are not well understood. Group-based interventions are sometimes offered but it is unknown whether this type of support is acceptable to men. Methods: Interviews with 17 men experiencing depression or anxiety. A further 12 interviews were conducted with staff who worked with depressed men (half of whom also experienced depression or anxiety themselves). There were detailed observations of four mental health groups and a mapping exercise of groups in a single English city (Bristol). Findings: Some men attend groups for support with depression and anxiety. There was a strong theme of isolated men, some reluctant to discuss problems with their close family and friends but attending groups. Peer support, reduced stigma and opportunities for leadership were some of the identified benefits of groups. The different types of groups may relate to different potential member audiences. For example, unemployed men with greater mental health and support needs attended a professionally led group whereas men with milder mental health problems attended peer-led groups. Barriers to help seeking were commonly reported, many of which related to cultural norms about how men should behave. General practitioners played a key role in helping men to acknowledge their experiences of depression and anxiety, listening and providing information on the range of support options, including groups. Men with depression and anxiety do go to groups and appear to be well supported by them. Groups may potentially be low cost and offer additional advantages for some men. Health professionals could do more to identify and promote local groups.